Single-incision Laparoscopic Sleeve Gastrectomy. Issue 4 (April 2013) - Mittermair, Reinhard; Pratschke, Johann; Sucher, Robert
Laparoscopic sleeve gastrectomy has gained popularity and acceptance among bariatric surgeons, mainly as a result of its low morbidity and mortality. Single-incision laparoscopic surgery (SILS), the most recent development in minimally invasive surgery, allows operations to be carried out through only a single incision using special ports. To further minimize the trauma of access incisions, we applied the SIL sleeve gastrectomy on a selected number of patients enrolled into our minimally invasive bariatric program. Between June 2010 and May 2012, 40 consecutive female patients underwent SIL sleeve gastrectomy. All data (demographic, morphologic, operative, and follow-up data) were prospectively collected in a computerized data bank. All patients were female. Mean age was 37 years (range, 19 to 62 years), preoperative body mass index was 40.8 kg/m 2 (range, 35.1 to 45.0 kg/m 2 ), and excess weight loss was 57.2 per cent at 6.6 months after surgery. Total operative time was 85 ± 21 minutes and mean hospital stay was 5 days (range, 4 to 24 days). Of the patients, two (5%) sustained postoperative complications such as leakage from the suture line and hemorrhage one in each case. There was no trocar site hernia. SIL sleeve gastrectomy seems to be an effective surgical option for the treatment of morbid obesity. During the first 6 months after the operation, weight loss was excellent. These results are at present comparable to those of multiport sleeve gastrectomy. SIL sleeve gastrectomy is safe and feasible and can be performed without changing the existing principles of this procedure.